Sequestration of the chloroquine receptor in cell-free preparations of erythrocytes infected with Plasmodium berghei. - Fitch, C D (1981)
When mouse erythrocytes infected with Plasmodium berghei were preincubated with [14C]chloroquine and then lysed by hypotonic shock, chloroquine remained bound to the resulting cell-free preparation. In an isotonic medium at pH 7.4 and 25 degrees C, chloroquine was bound to the cell-free preparation with an apparent dissociation constant of 1.8 x 10(-7) M. The bound [14C]chloroquine could be displaced by nonradioactive chloroquine, amodiaquine, quinacrine, and mefloquine, as would be predicted from knowledge of the specificity of ferriprotoporphyrin IX for antimalarial drugs. Also, as predicted, primaquine did not displace the [14C]chloroquine. The ability of these cell-free preparations to bind chloroquine with high affinity decreased rapidly with incubation at 37 degrees C and became undetectable within 1 h; at 4 degrees C the decrease occurred more slowly. This behavior of the endogenous receptor-chloroquine complex was duplicated by an exogenous ferriprotoporphyrin IX-chloroquine complex loaded into cell-free preparations of erythrocytes infected with P. berghei. These findings support the hypothesis that ferriprotoporphyrin IX is the endogenous chloroquine receptor of P. berghei and indicate that it can be sequestered rapidly in a form that is inaccessible to chloroquine.